Entrepreneurial ecosystems: what we know and where we move as we build an understanding of China. Issue 5 (26th May 2020) - Chen, Juanyi; Cai, Li; Bruton, Garry D.; Sheng, Naiheng
ABSTRACT: Scholars recognize entrepreneurial ecosystems of interconnected entrepreneurial actors, organizations, institutions, context, and entrepreneurial processes are critical to new venture success. Here we examine the burgeoning academic literature on entrepreneurial ecosystems in both the West and China to build a platform for the greater understanding of ecosystems, particularly as scholars expand its understanding in China. To build this understanding, we initially examine and classify the existing research in both leading international journals and Chinese journals on entrepreneurial ecosystems into four broad themes of nature, networks, institutions, and dynamics. We then build on this review of this literature to discuss how such findings inform scholars about the future research of ecosystems in China.